MORPHOLOGICAL AND PHYSIOLOGICAL CHANGES OF GROUNDNUT PLANTS BY FOLIAR APPLICATION WITH SALICYLIC ACID - G. Renuka; S.madhu (The Bioscan, 2022)
The purpose of this research is to examine the effects of salicylic acid applied topically to groundnut plants at concentrations of 100, 200, and 400 mg/L on the plant's vegetative development, photosynthetic pigment content, yield, and several biochemical components of groundnut grains, as well as the interactions between these factors. There was a positive correlation between plant growth characteristics and yield, according to the data. After adding 100 or 200 mg/L of salicylic acid (SA), groundnut grains exhibited an increase in total carbohydrates, lipids, and proteins. Results for yield and the aforementioned components were lowest when SA was administered at 400 mg/L in comparison to the control groups.